Mas-related G protein-coupled receptor MRGPRX2 in human basophils: Expression and functional studies - Toscano, Alessandro; Elst, Jessy; Van Gasse, Athina L.; Beyens, Michiel; van der Poorten, Marie-Line; Bridts, Chris H.; Mertens, Christel; Van Houdt, Michel; Hagendorens, Margo M.; Van Remoortel, Samuel; Timmermans, Jean-Pierre; Ebo, Didier G.; et al. (Frontiers in Immunology, 2023)
Background: Occupancy of MRGPRX2 heralds a new era in our understandings of immediate drug hypersensitivity reactions (IDHRs), but a constitutive expression of this receptor by basophils is debated. Objective: To explore the expression and functionality of MRGPRX2 in and on basophils. Methods: Basophils from patients with birch pollen allergy, IDHRs to moxifloxacin, and healthy controls were studied in different conditions, that is, in rest, after stimulation with anti-IgE, recombinant major birch pollen allergen (rBet v 1), moxifloxacin, fMLP, substance P (SP), or other potential basophil secretagogues. In a separate set of experiments, basophils were studied after purification and resuspension in different media. Results: Resting whole blood basophils barely express MRGPRX2 on their surface and are unresponsive to SP or moxifloxacin. However, surface MRGPRX2 is quickly upregulated upon incubation with anti-IgE or fMLP. Pre-stimulation with anti-IgE can induce a synergic effect on basophil degranulation in IgE-responsive subjects after incubation with SP or moxifloxacin, provided that basophils have been obtained from patients who experienced an IDHR to moxifloxacin. Cell purification can trigger a “spontaneous” and functional upregulation of MRGPRX2 on basophils, not seen in whole blood cells, and its surface density can be influenced by distinct culture media. Conclusion: Basophils barely express MRGPRX2 in resting conditions. However, the receptor can be quickly upregulated after stimulation with anti-IgE, fMLP, or after purification, making cells responsive to MRGPRX2 occupation. We anticipate that such “conditioned” basophils constitute a model to explore MRGPRX2 agonism or antagonism, including IDHRs originating from the occupation of this receptor.